Analysis of The Influence of Communication and Promotion in Digital Social Media on Citizens' Participation in The Election - Dharta, Firdaus Yuni; Beddu, Megawati; Salsabillah Putri, Chynika; Malik Ibrahim, Mozart; Hayati, Kumala (Jurnal Informasi dan Teknologi, 2024)
This research aims to provide conclusive results regarding interaction and discussion, use, and exploitation of social media in the context of general elections in the digital public space. This research involves analyzing all messages published by presidential candidates via social media during the general election campaign. Every day during the campaign, a presidential candidate published a tweet, thereby collecting data. The research results revealed that the general public's ability to participate in substantive political conversations related to the presidential election remains incomplete. The achievement of equality among participants in digital public spaces remains incomplete. Candidates focus more on their political messages and interactions with the media and their own political platforms rather than interacting equally with other users. The role of participants in digital public spaces is very relevant. Although the Internet provides a wealth of information, users tend to be disseminators rather than conducting in-depth analysis. This can hinder the formation of independent opinions and meaningful participation in political discussions. In this context, commercialization and excessive information on the internet can be detrimental to the process of creating a healthy public space. However, in reality, the internet has not been able to effectively overcome complex political challenges. In this context, it is important to develop a more critical understanding of the role of the internet in shaping the digital public sphere. This requires awareness of the challenges and complexities involved, as well as efforts to promote more active and educated participation in the digital public sphere.